2015
DOI: 10.1016/j.rehab.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Collection of normative data for spatial and temporal gait parameters in a sample of French children aged between 6 and 12

Abstract: The gait pattern in French children aged between 6 and 12 differs from those recorded elsewhere in the world; although gait parameters appear to change in much the same way with age worldwide, our values (even when normalized) are different. Our local database should be of value in French studies of childhood gait disorders. Given that gait patterns do not appear to mature by the age of 12, it would be valuable to study gait patterns in a population of teenagers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 15 publications
6
25
1
6
Order By: Relevance
“…A tentative answer is that the lateral ‘shrinking’ of the CoM trajectory, relative to body height, reflects the maturation of balance control. This is consistent with the results showing that the absolute width of the base of support is invariant (Thevenon et al , 2015) or even decreasing as age increases (Hallemans et al , 2018). The narrowing of the CoM path therefore makes oscillations over a support base safer as they become relatively narrower with body elongation.…”
Section: Discussionsupporting
confidence: 92%
“…A tentative answer is that the lateral ‘shrinking’ of the CoM trajectory, relative to body height, reflects the maturation of balance control. This is consistent with the results showing that the absolute width of the base of support is invariant (Thevenon et al , 2015) or even decreasing as age increases (Hallemans et al , 2018). The narrowing of the CoM path therefore makes oscillations over a support base safer as they become relatively narrower with body elongation.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, there was high or moderate intrasubject reliability of 10 MWT for all ages (ICC from 0.70 to 0.89), and the mean velocity in the fV10 condition is similar to those obtained in studies with typical children and adolescents [19,26]. There is a lack of comparable results about reliability in the literature involving typical children.…”
Section: Discussionsupporting
confidence: 50%
“…Characteristics of the 25 included studies comparing measures of balance performance in boys and girls are shown in Table 4. Twelve studies [22, 24, 45, 5664] examined variables of static steady-state balance, five studies [49, 6568] analyzed outcomes of dynamic steady-state balance, four studies [23, 52, 69, 70] examined outcomes of proactive balance, two studies [21, 71] reported proxies of both static and dynamic steady-state balance, and two studies [72, 73] scrutinized measures of static steady-state and proactive balance. No study reported outcomes of reactive balance.…”
Section: Resultsmentioning
confidence: 99%